On the current situation and development direction of the Business Administration of small and medium-sized enterprises in Xi'an, China - Ding, Zhaijuan (International Journal of Management and Education in Human Development, 2023)
With the gradual improvement of China's market economic system, China's small and medium-sized enterprises have played a very important role in the development of the social economy. To ensure the sustainable development of China's small and medium-sized enterprises, we must strengthen their industrial and commercial administration and fundamentally improve their economic benefits. Therefore, it is particularly important to do a good job in business administration. This paper mainly studies some problems existing in the industrial and commercial administration of Chinese small and medium-sized enterprises and the corresponding solutions. The results show that China's small and medium-sized enterprises have some defects in industrial and commercial administration, and need to adjust the system and introduce talents